Impact of Using Karplus Model to Develop Inferential Reasoning Skills and Legal Knowledge in Handball Among Students - Mohammed Faisal Mahdi Al-Janabi (Program Studi Pendidikan Kepelatihan Olahraga, 2026)
The research aims to identify on effect Model Carplus in development skills thinking inferential and knowledge For the articles of the law in ball hand I have The students, and the researcher assumed there were Differences The indication Statistics in The two tests Tribal Post-test for the experimental group In the variables in thinking inferential and knowledge Legal in ball hand I have The students. The researcher also used the experimental method as it was suitable for the nature of the research, and the researcher conducted his research on Students of the Faculty of Physical Education and Sports Sciences At university Samarra For the academic year 2024/2025, (68) students were chosen randomly. The participants were divided into three groups, and group (A) was chosen by lot to represent the experimental group. The researcher used statistical methods including the arithmetic mean, standard deviation, independent samples t-test, paired samples t-test, and percentage. The researcher concluded that the Karplus model had a positive effect. in development skills thinking inferential and knowledge Legal in ball hand I have The students, and the researcher also recommended emphasizing the importance of using the Karplus model in developing inferential thinking skills in handball and moving away from traditional methods that bring boredom and weak motivation towards learning, and using this model in other games.